Pengaturan Tindakan Memviralkan Seseorang Tanpa Izin Di Media Sosial Dikaitkan Dengan Hak Privasi Dalam Hukum Pidana Indonesia - Septiani, Kartika; Jayakusuma, Zulfikar; ., Elmayanti (Jurnal Ilmiah Wahana Pendidikan, 2023)
An act to viralizing someone on social media is phenomenon that arises due to the development of science and technology in Indonesia. This phenomenon has both positive and negative impact in society, one of the negative impacts is the emergence of a trend in society to viralizing other people in social media, which then violates the privacy of others. This viralizing action that violates other people's privacy rights does not yet have regulation in Indonesian positive law even though the right to privacy is a right that must be protected because it is part of human rights. Indonesia as a constitutional state has an obligation to carry out the task of protecting the human rights of its citizens, so it is necessary to regulate this phenomenon. Therefore, the purpose of this study is first, to find out the urgency and regulation of the act of making someone viral without permission on social media associated with the right to privacy. Second, to formulate appropriate legal reforms against the act of making someone viral without permission on social media associated with the right to privacy. This research is a normative legal research. It is also called doctrinal legal research, namely legal research that uses data based on library research by taking quotes from the literature that is related to the problem to be studied. Thus, this study uses secondary data sources consisting of primary, secondary, and tertiary legal materials. This study also uses qualitative analysis and produces descriptive data.From the results of the discussion and research conducted, there are several conclusions obtained, namely: First, the act of making other people viral without permission on social media is a violation of privacy that harms human rights and until now the Indonesian Criminal Code has not accommodated this act. Second, find the right categories of offenses and sanctions to criminalize this viralizing action that violates privacy into the Criminal Code by taking into account the outlook on life, awareness and legal ideals, as well as the Indonesian nation's philosophy originating from Pancasila the Preamble to the Constitution of the Republic of Indonesia 1945.